Concentration-triggered liquid-to-solid transition of sodium caseinate suspensions as a function of temperature and enzymatic cross-linking. (April 2020) - Raak, Norbert; Abbate, Raffaele Andrea; Alkhalaf, Mahmoud; Lederer, Albena; Rohm, Harald; Jaros, Doris
Abstract: Casein, the major milk protein fraction, is responsible for structure formation in fermented dairy products, and enzymatic cross-linking of caseins represents a possibility to modify texture and physical product properties. In this research, casein cross-linking by microbial transglutaminase (mTGase) was characterised from a colloid rheological perspective. Sodium caseinate (NaCn) at 50 g kg −1 was not (0 h), moderately (3 h) or excessively cross-linked (24 h) using 3 U mTGase per g protein, and subsequently freeze-dried and redissolved at 10–300 g kg −1 . The resulting suspensions were characterised in steady and oscillatory shear rheology to obtain viscosity-concentration plots and to evaluate shear thinning and viscoelastic properties. Additional molecular analysis was done by dynamic light scattering and asymmetric flow field flow fractionation, showing that NaCn molecules were associated to hydrated nanoparticles with hydrodynamic radii of ~12 nm and cross-linked predominantly within the same particle, leading to an increased apparent density of the particles with ongoing incubation. This resulted in a transition from soft particles towards a more hard sphere like behaviour in the rheological experiments. While concentrated suspensions of uncross-linked NaCn (0 h) showed properties of a viscoelastic liquid in frequency sweeps over the tested temperature range (5–40 °C), a true liquid-to-solid transition upon cooling was observed for the cross-linked samples. The threshold for this transition was lower for moderately (3 h) than for excessively cross-linked NaCn (24 h), i.e., at lower concentration and higher temperature, presumably because interpenetration of the particles was still possible to some extent. Graphical abstract: Image 1 Highlights: Sodium caseinate (NaCn) particles were internally cross-linked by transglutaminase. An increased apparent density was found by multi angle light scattering experiments. A transition from soft particles towards more hard sphere like behaviour was noticed. A true phase transition upon cooling was observed for cross-linked NaCn particles.